Using machine learning and qualitative interviews to design a five-question survey module for women's agency. (January 2023) - Jayachandran, Seema; Biradavolu, Monica; Cooper, Jan
Highlights: Surveys often aim to measure complex concepts with a few close-ended questions. We introduce a new method for selecting questions. The method identifies the survey questions that best correspond to answers given in a qualitative interview about the concept. We field many survey questions and use machine learning (ML) tools to find the questions that best predict the coded qualitative data. We apply the method to create a five-question survey module to measure women's agency in north India. The questions chosen are similar across three ML algorithms, and the resulting survey measure of women's agency performs well in diagnostics. Abstract: Open-ended interview questions elicit rich information about people's lives, but in large-scale surveys, social scientists often need to measure complex concepts using only a few close-ended questions. We propose a new method to design a short survey measure for such cases by combining mixed-methods data collection and machine learning. We identify the best survey questions based on how well they predict a benchmark measure of the concept derived from qualitative interviews. We apply the method to create a survey module and index for women's agency. We measure agency for 209 married women in Haryana, India, first, through a semi-structured interview and, second, through a large set of close-ended questions. We use qualitative coding methods to score each woman's agency based on the interview, which we use as a benchmark measure of agency. To determine the close-ended questions most predictive of the benchmark, we apply statistical algorithms that build on LASSO and random forest but constrain how many variables are selected for the model (five in our case). The resulting five-question index is as strongly correlated with the coded qualitative interview as is an index that uses all of the candidate questions. This approach of selecting survey questions based on their statistical correspondence to coded qualitative interviews could be used to design short survey modules for many other latent constructs.